TAMAN SATWA BORNEO DI ARANIO, KABUPATEN BANJAR - Annisa Rakhmatillah; Pakhri Anhar (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
The need of an animal park as a place or ex-situ conservation institution, a means of protection and preservation of wild animals that are protected or not through rescue activities, collecting, maintaining the welfare of the new habitat and demonstrating to the public as a means of education. In the design of the Wildlife Park there must be an approach to the habitat of animals for animal welfare, then the need for habitat landscape simulation in the design of the Wildlife Park. By applying the programmatic concept of Landscape Immersion in this design which is related to landscape simulation and psychology of animals and humans in animal parks. This concept applies to the arrangement of space and continuous circulation. so visitors feel as if they are visiting an animal's natural habitat, with all its sights, sounds and smells.